STUDENTS’ SPEAKING ANXIETY IN BASIC SPOKEN ENGLISH - Maulida Rahmah; Faida Azhimia (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aimed to describe about the factors that caused students’ speaking anxiety and the students’ strategies to reduce the anxiety in basic spoken English class. The participants of the study were 18 students who took basic spoken English class in the first semester. The method used in this study was descriptive qualitative. The data were obtained from interviews and observation. The findings revealed that the students’ speaking anxiety in basic spoken English was derived from some factors provoked by both internal and external matters. The first factor was type of task. The task became something that causes anxiety if the students’ were asked to present the activities in front of the class. The second was fear of making mistakes. All the students felt the same thing about their anxious feeling when they made mistakes. The third was the role of language teachers. It was related to how teachers create a classroom atmosphere that was suitable for the teaching and learning process. The fourth factor was self-perception, self-perception in this context is a perception that causes a negative effect on students. The last factor was limited exposure to English. Limited exposure to English in their environment impedes the development of their communicative proficiency. The results of this study also found that there were good strategies which they applied to reduce anxiety. The first was the preparation before learning English, it helped students to feel better because they had material that they could use for the learning. The second strategy was positive thinking. Positive thinking as a psychological factor was needed to cope the language anxiety and to lose a fear of being anxiety in the classroom. The last strategy that they used was peer seeking. It was often done by the students. The students liked to ask a friend if there was something that they did not understand